A preliminary empirical validation of an incremental approach to constructing component-based systems directly from natural language requirements - Nordin, Azlin; Salleh, Norsaremah; Abdullah, Lili Marziana (2014)
Software development process in general starts with Requirements Engineering (RE) process. During the RE process, requirements are identified, analyzed and relevant information is modelled into representation that could be further used by the development team. These processes involve abstraction processes at various levels of details according to the chosen software development methodology. In addition, the design decisions are largely contributed by the experiences of the development team. Hence, an incremental approach has been defined in [1], [2] to propose a systematic way of constructing component-based systems from natural language requirements (NLR). This paper describes an experiment to further evaluate the incremental approach in the view of correctness.